Mindfulness Training among Individuals with Parkinson’s Disease: Neurobehavioral Effects - Barbara Pickut; Sven Vanneste; Mark A. Hirsch; Wim Van Hecke; Eric Kerckhofs; Peter Mariën; Paul M. Parizel; David Crosiers; Patrick Cras (Parkinson's Disease)
Objective. To investigate possible neurobehavioral changes secondary to a mindfulness based intervention (MBI) training for individuals living with Parkinson’s disease (PD). Background. In the context of complementary medicine, MBIs are increasingly being used for stress reduction and in patient populations coping with chronic illness. The use of alternative and complementary medicine may be higher in patients with chronic conditions such as PD. However, behavioral effects of mindfulness training in PD have not yet been reported in the literature and this points to an unmet need and warrants further examination. Methods. A total of 27 out of 30 PD patients completed a randomized controlled longitudinal trial. Questionnaires and the UPDRS I–IV were obtained at baseline and 8-week follow-up. Results. Significant changes after the MBI were found including a 5.5 point decrease on the UPDRS motor score, an increase of 0.79 points on Parkinson’s disease questionnaire (PDQ-39) pain item, and a 3.15 point increase in the Five Facet Mindfulness Questionnaire observe facet. Conclusions. To the best of our knowledge, this is the first quantitative analysis of neurobehavioral effects of MBI in PD.